Analysis Of Multiphase Transformer Supplying A Static And Dynamic Load - Nor Azizah, Mohd Yusoff; Kasrul, Abdul Karim; Sharin, Ab Ghani; Fazlli, Patkar; Siti Azura, Ahmad Tarusan; Auzani, Jidin (Asian Research Publishing Network (ARPN), 2016)
Transformers are able to step up or step down an output voltage from their input. It also can be used to directly supply an electrical motor when a constant frequency operation is required. Here, the research is focusing on designing a three-to-five phase transformer that acts as static phase converters for supplying a balance five-phase load. The designing process of the transformer is described based on the graphical phasor diagram that is flexible and easy to be implemented. At the end, the performances of the designed transformer are evaluated using a static and dynamic load. The designed three-to-five phase transformer is able to maintain a balance five phase voltage for several type and level of load as shown in experimental result.